Paraneoplastic progressive encephalomyelitis with rigidity and myoclonus associated with monoclonal B-cell lymphocytosis in the setting of longstanding methotrexate use: case report - Jia, Fangzhi (Frank); Amin, Mohammad Ruhul; Kwon, Gi Tae; Mousapasandi, Amir; Dai, Pei; Kitson, Jed; Selim, Adrian; Ip, Jerome (Frontiers in Immunology, 2024)
Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a rare but debilitating disease within the stiff person syndrome (SPS) spectrum characterised by muscle rigidity, spasms, myoclonus, dysautonomia, and brainstem dysfunction. The exact pathogenetic mechanism is unclear, although there is an association with the presence of glycine receptor antibodies in serum and cerebrospinal fluid, and some cases are paraneoplastic. Here, we report a case of paraneoplastic, glycine receptor antibody-positive PERM associated with an otherwise subclinical monoclonal B-cell lymphocytosis (MBL) of the non-CLL phenotype, which may be, in turn, likely secondary to long-term methotrexate use [i.e., methotrexate-associated lymphoproliferative disorder (MTX-LPD)] or an underlying autoimmune disease. Treatment with multiple lines of initial induction immunomodulatory therapies, followed by maintenance rituximab, achieved long-term remission of the neurologic, haematological, and rheumatologic disease. This is, to our knowledge, the first reported association between PERM and MBL, or between PERM and MTX-LPD.